THE FREQUENT ERRORS OF THE STUDENTSâ WRITING OF WIDYA DHARMA UNIVERSITY KLATEN IN ACADEMIC YEAR 2014/2015 - Widayanti, Sukasih Ratna (MAGISTRA, 2016)
The purpose of this study is to identify frequent errors in the written texts made by students ofWidya Dharma University Klaten in academic year 2014/2015. This study was categorized into a case studysince it limited the participants to the students of second semester in Widya Dharma University Klaten. Thedata sources of the research were written texts made by the students. The data were studentsâ errors, whichwere analyzed through classification, frequency counting, and description.The finding of the study shows that there were forty three errors made by the students in their writtentexts. These errors can be classified into eleven types of errors. These are associated with the use of verbs(25.6%), punctuations (4.6%), articles (16.3%), prepositions (2.3%), plural/singular nouns (14%), spellings (14%),pronouns (9.4%), parts of speech choices (4.6%), word orders (2.3%), word choices (4.6%), and miscellany(2.3%). The most frequent error is related to the verb uses and the least frequent errors are related to theprepositions, word orders, and miscellany.Keyword : error, writing, students writing